APPLYING TEAM ASSISTED INDIVIDUALIZATION FOR INCREASING MATHEMATICS LEARNING INTERACTION - Syarif Rijaludin; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The level of activity the students became a benchmark of success in learning. Student learning interactions are still low. This research aims to increase mathematics learning interaction using cooperative learning model type Team Assisted Individualization (TAI) grade VII C of even semester at State Junior High School 2 (SMP Negeri 2) Bantul Regency 2017/2018 the school year amounted to 32 students. The technique of data collection by observation and interview. Data collection instruments using sheets of observation, interview guidelines, and triangulation. The data analysis technique using data analysis, the results of observation, interviews, and data analysis triangulation. The results showed an increase in student learning interaction in the learning of mathematics. This is proven by the data observations on learning mathematics that has increased at every cycle, i.e., the average percentage in cycle I of 49.95% criteria enough. In cycle II, it increased to 66.90% with the criteria either.Â